The Influence of Communication on Employee Engagement Through Job Satisfaction of MSMEs in Jakarta - Rahmawati, Sevia; Perkasa, Didin Hikmah (JMK (Jurnal Manajemen dan Kewirausahaan), 2026)
This study analyzes how communication affects employee engagement through job satisfaction in small businesses in Jakarta. Quantitative techniques using the SmartPLS 4.0 application were applied in this study. Data was obtained from an online survey given to 150 people working in various small businesses in Jakarta. The findings show that good communication helps increase job satisfaction and employee engagement levels. In addition, job satisfaction itself helps increase employee engagement. This study also found that job satisfaction acts as an intermediary step between communication and employee engagement, meaning that communication helps increase job satisfaction, which in turn helps increase engagement. Overall, this study shows that clear communication is key to making employees happier and more engaged. By improving communication within their companies, small businesses in Jakarta can build a better, more productive, and more focused work environment.